Efektivitas Pembelajaran Jarak Jauh Berbasis Teknologi Digital Terhadap Pencapaian Nilai Fiqih Siswa Madrasah Ibtidaiyah - Jannah, Kholifatul; Rahayu, Yayuk Sri; Muzdalifah, Muzdalifah (Impressive: Journal of Education, 2024)
This study aims to analyze the effectiveness of distance learning based on digital technology on the achievement of fiqh scores at MI Nurul Hidayah Surabaya. The approach used is qualitative with a descriptive method. Data was collected through in-depth interviews, participatory observation, and document analysis. The results show that the use of Google form as an online learning medium is highly effective in supporting the fiqh teaching and learning process, evidenced by the high average student score of 12.13. Despite challenges in technology infrastructure and students' digital literacy, the use of Google form yielded positive results, especially with the active support from parents. This study concludes that distance learning based on digital technology can improve the quality of education at MI Nurul Hidayah Surabaya, particularly in the subject of fiqh, provided that infrastructure and training for students and teachers are enhanced.